NILAI FILOSOFIS PROSES KHITBAH DAN MENENTUKAN MAHAR PERKAWINAN UNTUK PEREMPUAN DALAM TINJAUAN FEMINISME ISLAM (TAFSIR AL-BAQARAH : 235-237 DAN AN-NISAA' : 4) - Salma Al Zahra Ramadhani; Muhammad Chairul Huda (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2023)
The dowry is a gift made by the bridegroom to the bride with an obligatory law but it's not mentioned in the form and type, large and small both in the Qur'an and in the hadith and khitbah as a statement made by a man to a woman by expressing a desire to marry a woman as her life partner. This is seen in the perspective of Islamic feminism by interpreting the verses of the Qur'an to obtain the meaning of gender justice, this is because the interpretation that has been done traditionally is sometimes still gender biased and makes men superior. The method used is a descriptive qualitative method with research that explains the reality of the understanding of a social phenomenon that occurs in society and discussed in more detail. This study states that long before there was an issue of gender quality, the verses of the Qur'an glorified women, had long before paid attention to the position of women with the interpretation of Q.S An-Nisaa' : 4 about giving dowry Q.S. Al-Baqarah : 235 about the khitbah process and Q.S. Al-Baqarah : 236-237 about Mut'ah given to women who were given away.